Metal–Organic Nanomaterial: Temperature Dependence of the STM Morphology and Electronic Level Structure of Silver‐Containing DNA (Small 5/2020). Issue 5 (6th February 2020) - Fardian‐Melamed, Natalie; Eidelshtein, Gennady; Rotem, Dvir; Kotlyar, Alexander; Porath, Danny
Abstract : In article number 1905901, Alexander Kotlyar, Danny Porath, and co‐workers use scanning tunneling microscopy and spectroscopy to study the morphology and electronic level structure of silver‐containing DNA at different temperatures, finding strong temperature dependence of the level spectra and hence the scanning tunneling microscopy apparent height of this nanostructure.